ANALISIS BUDAYA ORGANISASI MODEL OCAI (ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT) DAN MOTIVASI KERJA HIRARKI KEBUTUHAN ABRAHAM MASLOW KARYAWAN PADA PT TELEKOMUNIKASI INDONESIA, TBK BOGOR - Indrawati, Nina Sri; Pratama, Dimas Aditya (Universitas Pakuan, 2015)
ABSTRACTThis study aims to determine the organizational culture analysis models OCAI (Organizational CultureAssessment Instrument) and work motivation Abraham Maslows hierarchy of needs of employees. PTTelekomunikasi Indonesia, Tbk Bogor located at Jalan Raya Padjadjaran No. 39 Bogor, West Java. Thecompany is engaged in the field of information and communication as well as service providers andtelecommunications network is complete in Indonesia. The problem lies on how to apply the normalbehavior in the company, is in conformity with the architecture leadership and corporate culture or not.Therefore, it is necessary to ensure appropriate analysis using models OCAI and Abraham Maslowshierarchy of needs. The results showed that the company makes adokrasi culture and culture as a keymarket that is used by companies to evaluate all kinds of internal and external problems. Advice given tothe company is doing the application of organizational culture can play an important role for thecompany and pay attention to all the needs required employees to help improve the performance of thecompany.Keywords: Analysis, Organizational Culture, OCAI, Motivation, Hierarchy of Needs, Abraham Maslow.